KOLONI JAMUR ANTAGONIS Trichoderma spp PADA BEBERAPA MEDIA TUMBUH SECARA IN VITRO - Haperidah Nunilahwati; Yani Purwanti; Khodijah .; Laili Nisfuriah; Joni Philep Rompas (Universitas Tridinanti Palembang, 2017)
Trichoderma is an antagonist biological agent in some fungal pathogens that cause many plant diseases in farmland. The effort to multiply Trichoderma fungi in vitro may use some media material. The appropriate medium is a prerequisite for studying microorganisms in different environments. The study aims to determine the development of Trichoderma fungal colonies in a macroscopic way in some media. The research was conducted in the laboratory of Plant Pest and Disease Faculty of Agriculture Palembang University from September to November 2017. The research was carried out by stages of preparation of isolates, media preparation and Trichoderma fungus inoculation on potato media, cassava media, sweet potato media, rice media, corn and green bean media. Observation of macroscopic colony development was done 6 days after inoculation (hsi), ie density and colony color, then identified, and data were analyzed descriptively. The results showed that Trichoderma fungi developed in potato media, cassava media, sweet potato media, rice media, corn media and green bean media. Trichoderma fungal colonies on potato media, sweet potato media, green bean medium is more dense than in cassava media, rice media and corn media. Trichoderma fungal colonies form a circle with clear boundaries, colony color was dark green and bright green with white side colonies on all media.Keywords: Fungal colonies, biological agents, Trichoderma, media, in vitro